(untitled) (Scientific journal of the Fergana State University, 2026)
This scientific study investigated the effect of different planting densities and defoliant rates on the seed quality of the medium-fiber cotton variety S-7303. During the research, planting densities of 70-80, 100-110, and 130-140 thousand plants per hectare, as well as Baystar defoliant rates of 0.500, 0.600, and 0.700 l/ha, were applied. The experimental results showed significant differences in kernel yield, 1000-seed weight, and seed oil content depending on the changes in planting density and defoliant rate. The optimal results were obtained under a planting density of 100-110 thousand plants per hectare and a defoliant rate of 0.600 l/ha. Under these conditions, the kernel yield, 1000-seed weight, and seed oil content remained within the standard limits.